2022
DOI: 10.1039/d2tb01436j
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nanoreactors with nutrient consumption and ROS generation capabilities for antibacterial and skin repair

Abstract: Bacterial wound infection has brought a serious threat to human health and caused huge economic losses. Attempts to develop biomaterials with excellent antibacterial effects are meaningful to promote wound healing....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According to several studies, different malignant tumors have higher Cu contents than normal tissues 34 . Cu can stimulate angiogenesis, 35 which is necessary for the growth and metastasis of tumors, by activating angiogenic proteins like angiopoietin (Ang), vascular endothelial growth factor (VEGF), 36–39 fibroblast growth factor 1 (FGF1), 40 and interleukin‐1 (IL‐1), and promote angiogenesis 41–44 . Therefore, Cu‐ exhaustion‐related cancer therapy emerges at the historic moment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several studies, different malignant tumors have higher Cu contents than normal tissues 34 . Cu can stimulate angiogenesis, 35 which is necessary for the growth and metastasis of tumors, by activating angiogenic proteins like angiopoietin (Ang), vascular endothelial growth factor (VEGF), 36–39 fibroblast growth factor 1 (FGF1), 40 and interleukin‐1 (IL‐1), and promote angiogenesis 41–44 . Therefore, Cu‐ exhaustion‐related cancer therapy emerges at the historic moment.…”
Section: Introductionmentioning
confidence: 99%
“…34 Cu can stimulate angiogenesis, 35 which is necessary for the growth and metastasis of tumors, by activating angiogenic proteins like angiopoietin (Ang), vascular endothelial growth factor (VEGF), [36][37][38][39] fibroblast growth factor 1 (FGF1), 40 and interleukin-1 (IL-1), and promote angiogenesis. [41][42][43][44] Therefore, Cu-exhaustion-related cancer therapy emerges at the historic moment. However, with the deepening of research, researchers have shown that Cu buildup can potentially result in cell death or irreversible harm to cells, such as cuproptosis, [45][46][47] apoptosis, 48,49 pyroptosis, 50,51 and ferroptosis.…”
mentioning
confidence: 99%
“…6,7 As an emerging therapeutic method, chemodynamic therapy (CDT) can be triggered by catalyzing endogenous overexpressed H 2 O 2 into hydroxyl radicals ( OH) via Fenton/Fenton-like reactions based on transition metal elements (e.g., Fe, Cu, Mn), exhibiting high tumor microenvironment specificity and biosafety, and has been of wide interest. [8][9][10][11] It is worth noting that the therapeutic effects of CDT can be constrained by finite H 2 O 2 concentrations and an unbreakable tumor antioxidant system. 12 In this regard, Cu 2+ ions are suitable for CDT, because they can react with overexpressed antioxidant glutathione (GSH) in a tumor microenvironment, and the generated Cu + ions further efficiently catalyze a Fenton-like reaction in weakacid media.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infection is a huge threat to wound healing, causing a delay in the healing process. [1][2][3] Severe bacterial infection can lead to tissue damage and even death. 4,5 As representatives of traditional dressings, bandages, and gauze have an extremely high usage rate in clinical treatment due to their convenience.…”
Section: Introductionmentioning
confidence: 99%